PhysioFormer: Integrating multimodal physiological signals and symbolic regression for explainable affective state prediction - Zhifeng Wang; Wanxuan Wu; Chunyan Zeng; Jialiang Shen (PLoS ONE, 2025)
As affective computing becomes increasingly crucial in health monitoring and psychological intervention, accurately identifying affective states is a key challenge. While traditional machine learning models have achieved some success in affective computation, their ability to handle complex, multimodal physiological signals is limited. Most affective computing tasks still rely heavily on traditional methods, with few deep learning models applied, particularly in multimodal signal processing. Given the importance of stress monitoring for mental health, developing a highly reliable and accurate affective computing model is essential. In this context, we propose a novel model—PhysioFormer, for affective state prediction using physiological signals. PhysioFormer model integrates individual attributes and multimodal physiological data to address inter-individual variability, enhancing its reliability and generalization across different individuals. By incorporating feature embedding and affective representation modules, PhysioFormer model captures dynamic changes in time-series data and multimodal signal features, significantly improving accuracy. The model also includes an explainability model that uses symbolic regression to extract laws linking physiological signals to affective states, increasing transparency and explainability. Experiments conducted on the Wrist and Chest subsets of the WESAD dataset confirmed the model’s superior performance, achieving over 99% accuracy, outperforming existing SOTA models. Sensitivity and ablation experiments further demonstrated PhysioFormer’s reliability, validating the contribution of its individual components. The integration of symbolic regression not only enhanced model explainability but also highlighted the complex relationships between physiological signals and affective states. Future work will focus on optimizing the model for larger datasets and real-time applications, particularly in more complex environments. Additionally, further exploration of physiological signals and environmental factors will help build a more comprehensive affective computing system, advancing its use in health monitoring and psychological intervention.